Characterization techniques for polymer nanocomposites - Mittal, Vikas (Wiley-VCH, 2012)
With its focus on the characterization of nanocomposites using such techniques as x-ray diffraction and spectrometry, light and electron microscopy, thermogravimetric analysis, as well as nuclear magnetic resonance and mass spectroscopy, this book helps to correctly interpret the recorded data